Effects of Yinzhihuang Granules on Serum Liver Enzymes in Jaundice Patients: A Real-World Study Based on HIS Data. (5th November 2020) - Zhang, Cheng; Zhang, Lidan; Lyu, Jian; Xie, Yanming; Xie, Yuting
Abstract : Objective . Our aim was to analyze the influence of Yinzhihuang granules on serum liver enzymes in jaundice patients and to provide real-world evidence for the efficacy evaluation of Yinzhihuang granules in treating jaundice. Methods . We constructed a data warehouse which integrates real-world electronic medical records from the hospital information system of multiple 3A hospitals in China and used a descriptive statistical method to analyze the changes in the serum liver enzymes of the jaundice patients treated with Yinzhihuang granules and then used Wilcoxon signed-rank to test the changes in the indicators caused by the treatment. Results . After being treated with Yinzhihuang granules, the jaundice patients had a decrease in the average serum levels of total bilirubin, indirect bilirubin, aspartate aminotransferase, glutamyl transpeptidase, and alkaline phosphatase, and the differences were statistically significant (P < 0.05 ) but had no significant changes in the average serum levels of direct bilirubin and alanine aminotransferase (P > 0.05 ). Conclusion . The data analysis on the real-world electronic medical records demonstrate that Yinzhihuang granules help to reduce jaundice patients' serum levels of total bilirubin, indirect bilirubin, aspartate aminotransferase, glutamyl transpeptidase, and alkaline phosphatase, but there is no evidence that Yinzhihuang granules help to reduce the jaundice patients' serum levels of direct bilirubin and alanine aminotransferase.